Factors affecting housing maintenance cost in Penang, Malaysia: Apartment Idaman Lavender 3, Idaman Lavender 4 and Tunas Residence in Penang / Nur Syafawati Johari and Alia Abdullah Saleh - Johari, Nur Syafawati; Saleh, Alia Abdullah (2018)
Housing is a basic need for all. The increasing number of population and income had an increase in housing demand. Thus, it has led to the construction of apartments to meet the needs of people and to reduce the use of land to build residential buildings. From year to year, maintenance costs of the building have increased. It is important to determine the factor that influences the housing maintenance cost of the apartment. One way to do it is by ensuring the maintenance cost of housing such as apartment residence maintenance is reduced. This study is to determine key factor that affect housing maintenance cost. The first objective of this study was to identify the factors that affect housing maintenance cost in Penang, the second objective was to rank the factor that affect housing maintenance cost in Penang and the last objective is to propose the recommendations on the factors identified which affect the housing maintenance cost. To achieve the objectives of the study, the questionnaires were distributed to the parties involved in the maintenance management of the building. A total of 50 questionnaires were distributed to relevant respondents such as building managers or supervisors, and maintenance management staff. In total, 30 completed questionnaires formed a database for descriptive and ranking analysis. Results of this study concluded that there are five dominant factors that affecting housing maintenance cost which are high expectations from tenants, building services, vandalism from tenants, inability to access the property or housing facilities and delay and failure reporting the problems from the tenants.